Prospective Evaluation of a Commercial Dengue NS1 Antigen Rapid Diagnostic Test in New Caledonia - Enagnon Kazali Alidjinou; Sylvie Tardieu; Isabelle Vrenken; Didier Hober; Ann-Claire Gourinat (Microorganisms, 2022)
Dengue virus infection is endemic in New Caledonia, with outbreaks occurring every year. We evaluated the Biosynex® Dengue NS1 antigen rapid diagnostic test (RDT) for the early diagnosis of dengue in patients attending a local hospital in northern New Caledonia. Samples collected from patients suspected of dengue infection were tested with RDT at the local laboratory, and then sent to the reference laboratory for confirmation with real-time RT-PCR. A total of 472 samples were included during the study period. RT-PCR yielded a positive result in 154 samples (32.6%). The sensitivity and specificity of the NS1 antigen RDT were 79.9% and 96.2%, respectively. The performance of the RDT varied by the time of sampling and dengue virus serotype. In conclusion, Biosynex® Dengue NS1 antigen RDT showed a sensitivity and a specificity in the upper range usually reported for this type of test. Several factors can lead to a suboptimal sensitivity, and negative samples with suggestive clinical features should be retested with reference methods.